A Simulation Study of Single Event Burnout (SEB) in a High-Voltage Pin Diode - Masume Soleimaninia (فصلنامه علوم و فناوری فضایی)
Exposure to ionizing radiation in space can potentially destroy electronic devices due to single-event effects (SEEs). Developing modern space technology requires high-voltage devices to supply the increased electric power demand. A widely recognized problem for power electronic devices in space is Single Event Burnout (SEB), which is a destructive form of SEE. SEB is a catastrophic failure in a high-voltage device initiated by the passage of high-energy particles during the device's OFF state (reverse bias). Consequently, these devices may lose their performance in space applications.This research investigates the occurrence of SEB in a high-voltage PiN diode through simulation using the Silvaco TCAD tool. The necessity of this investigation stems from the increased use of high-voltage components in spacecraft. To achieve this, a PiN diode with a breakdown voltage of 3.3 kV was simulated in the Silvaco TCAD tool, considering the appropriate physical models. Subsequently, the diode's characteristic curve was obtained.In the next step, an incident beam with varying values of Linear Energy Transfer (LET) related to carbon ions was irradiated onto the diode. The variations in carrier concentration, current, and electric field were studied. The results indicate that when ions strike the diode, the electric field increases up to five times, and the concentration of carriers rises significantly, leading to a sharp increase in device current and a temperature rise to 1800 K, beyond the melting point of silicon. This condition suggests failure due to burnout from local heating caused by the multiplication of ion-generated carriers in the simulated PiN diode, which is consistent with earlier research experiments. Based on these results, the capability of the Silvaco tool in simulating SEB has been confirmed.